Intertextuality between Malin Kundang Legend and Malin Kundang Menggugat’s Drama Script - Yanti, Prima Gusti; Zabadib, Fairul; Safiic, Imam (Opción, 2019)
This article aims to describe the intertextuality contained in the legend of Malin Kundang (MK) with the drama script of Malin Kundang Sues (MKS) by Sinar Hadi. The method used is content analysis to describe data objectively and systematically. As a result, expansion is an improvement or development of a hypogram, whereas conversion is a reversal of the hypogram or matrix. In conclusion, the shift in cultural background occurred in Malin Kundang's legend.